Failure Investigation of High-Chromium Cast Iron Rolls - Espenido, Mercurio I. (Philippine Engineering Journal; Vol 18 No 2 (1997), 2021)
An investigation was made to look into the factors causing premature failures in high-chromium cast iron rolls. It has been verified that fire cracking which results from thermal fatigue serves as failure initiation sites and thus greatly limits the service life of rolls. Thermal fatigue mechanism is described and how it progresses to barrel breakage and spalling.